Impacts of climate change on predicted habitat suitability and distribution of Djaffa Mountains Guereza (Colobus guereza gallarum, Neumann 1902) using MaxEnt algorithm in Eastern Ethiopian Highland - Chala Adugna Kufa (Global Ecology and Conservation, 2022)
Understanding the impacts of climate change, landscape composition, topographic attributes, and anthropogenic disturbance on wildlife distribution is critical to selecting prior conservation areas and to executing successful management plans. Habitat suitability mapping aims to predict species' ecological niches and ranges using these factors as predictors. There has been no study of the potentially suitable habitat for the data-deficient Djaffa Mountains Guereza and the factors affecting its distribution in the Ahmar Mountains. The objective of this study was to predict the habitat suitability and distribution models of Djaffa Mountains Guereza in eastern Ethiopian highland under different climate change scenarios using maximum entropy (MaxEnt) model. We used 47 occurrence datasets assembled between 2020 and 2021 and 10 ecological predictor variables processed in geographical information systems and R software. We found that 133,604.52 ha (1.77%) of the 753, 0749.39 ha study area is suitable habitat for the Djaffa Mountains Guereza, of which 18,326.12 (13.33%) ha were highly suitable, whereas the remaining area was moderately suitable. Our models also showed that precipitation of the wettest quarter had the highest contribution to predicting the habitat suitability (65.90%), followed by land cover (17.40%). Habitat suitability was directly related to precipitation seasonality and the precipitation of the wettest quarter, while it is indirectly related to temperature seasonality and the temperature mean diurnal range. The models showed the overall gain in the suitable habitat of Djaffa Mountains Guereza under all future climate scenarios, however, the projected habitat distribution show fragmentation. Our habitat suitability and distribution models provide critical information for the conservation and management of Djaffa Mountains Guereza by recommending stocking of the fragmented forests, assessment of conservation challenges, and mitigations of climate change. A comprehensive population assessment throughout their restricted distribution is also crucial to understand conservation status and population size.